1997
DOI: 10.1128/iai.65.1.101-109.1997
|View full text |Cite
|
Sign up to set email alerts
|

Identification and characterization of a novel PrfA-regulated gene in Listeria monocytogenes whose product, IrpA, is highly homologous to internalin proteins, which contain leucine-rich repeats

Abstract: The expression of all virulence factors in Listeria monocytogenes characterized to date is controlled by the virulence regulator protein, PrfA. To identify further PrfA-regulated proteins, we examined supernatants of L. monocytogenes EGD harboring additional copies of the PrfA regulator for the presence of novel proteins. This led to the identification and biochemical purification of a hitherto uncharacterized PrfA-dependent 30-kDa protein (A. Lingnau, T. Chakraborty, K. Niebuhr, E. Domann, and J. Wehland, Inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0
1

Year Published

1998
1998
2007
2007

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(30 citation statements)
references
References 38 publications
0
29
0
1
Order By: Relevance
“…InlA associates with the bacterial cell wall via a conventional cell wall anchoring sequence , while the cell wall association of InlB requires a larger segment, comprising the last 232 amino acids of the C-terminus (Braun et al, 1997). A striking structural feature of both proteins is the presence of consecutive leucine-rich repeats (LRRs), present 15 times in InlA and seven times in InlB (Lingnau et al, 1995;Domann et al, 1997). Homology searches have revealed that InlA and InlB are members of a superfamily of LRR-containing proteins.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…InlA associates with the bacterial cell wall via a conventional cell wall anchoring sequence , while the cell wall association of InlB requires a larger segment, comprising the last 232 amino acids of the C-terminus (Braun et al, 1997). A striking structural feature of both proteins is the presence of consecutive leucine-rich repeats (LRRs), present 15 times in InlA and seven times in InlB (Lingnau et al, 1995;Domann et al, 1997). Homology searches have revealed that InlA and InlB are members of a superfamily of LRR-containing proteins.…”
Section: Introductionmentioning
confidence: 99%
“…These LRRs are found only in pathogenic bacteria, such as the ipaH gene family in Shigella flexneri, the YopM protein from Yersinia pestis, the filamentous haemagglutinin protein of Bordetella pertussis and the TpLRR protein of Treponema pallidum (Kobe and Deisenhofer, 1994;Makhov et al, 1994;Shevchenko et al, 1997). It has been shown that pathogenic Listeria also harbours an internalin-like protein gene (irpA), encoding a secreted protein of 30 kDa (Engelbrecht et al, 1996;Lingnau et al, 1996;Domann et al, 1997). Recently, four more internalin-like proteins have been found in L. monocytogenes, although the role of these proteins in infection is at present unclear .…”
Section: Introductionmentioning
confidence: 99%
“…The Escherichia coli strain InvKFP was grown in Luria-Bertani (LB) broth at 37³C; Listeria strains analysed in this study were grown in brain heart infusion broth at 37³C. The L. monocytogenes wildtype strain EGD and ¢ve di¡erent deletion mutants of this strain were used: virpA3 [11]; v£aR (161 of the 177 amino acids comprising FlaR polypeptide were deleted (E. Busch, personal communication)); vactA-plcB [12]; PprfABox (deletion of the 12 bp long PrfA box 5P-TAACATAAGTTA-3P upstream of the inlAB operon (A. Darbouche, unpublished data)); vinlFDE (deletion of the gene cluster inlFDE apart from the ¢rst 16 amino acids of InlF and the last 78 amino acids of InlE (A. Darbouche, unpublished data)). All these deletion mutants have an ar-ti¢cial chromosomal NotI restriction site in common and were generated as previously described [13].…”
Section: Bacterial Strainsmentioning
confidence: 99%
“…To date, three di¡erent gene clusters encoding virulence factors, the prfA-plcA-hly-mpl-actA-plcB, inlAB, and the inlFDE genes on the chromosome of L. monocytogenes have been described ( [4], A. Darbouche, unpublished data). Two other genes, £aR and irpA, have been shown to be associated with virulence but are organised on the chromosome as individual genes [11,18]. We wished to determine the relative order of these genes and to locate them to speci¢c regions on the chromosome.…”
Section: Mapping Of Virulence Genes On the Chromosomementioning
confidence: 99%
“…Both InlA and InlB are relatively large, cell wall-anchored surface proteins. We and others have previously cloned and characterized a novel member of the internalin multigene family (Engelbrecht et al, 1996;Domann et al, 1997) encoding a small, secretory protein termed InlC (or IrpA). The inl C gene is expressed in the cytoplasm of phagocytic J774 cells at late stages of an infection (Engelbrecht et al, 1996).…”
Section: Introductionmentioning
confidence: 99%